Efektivitas penyuluhan gizi berbasis prinsip B2SA terhadap tingkat pengetahuan ibu dalam upaya pemenuhan gizi seimbang bagi balita - Puteri, Hidayatusy Syukrina; Kustiani, Ai; Astuti, Dewi Woro; Harvidea, Radella; Nurhartanto, Adhi (JOURNAL of Public Health Concerns, 2026)
Background: Indonesia still faces the serious challenge of triple burden malnutrition, particularly in rural areas such as Hajimena Village, South Lampung. Limited access to nutrition information and suboptimal utilization of local foods are major obstacles to toddler feeding practices. The principle of Diverse, Nutritious, Balanced, and Safe Food (B2SA), as outlined in the "Isi Piringku" concept, presents a strategic approach to address this issue. Purpose: To evaluate the effectiveness of nutrition counseling and the level of maternal knowledge based on the B2SA principle, utilizing the potential of local foods to meet balanced nutrition needs for toddlers. Method: The activity was conducted on Wednesday, January 21, 2026, at the Cemara Kebun Bibit Integrated Health Post (Posyandu), Hajimena Village, South Lampung Regency. This study used a one-group pre-test and post-test design. A sample of 36 respondents was drawn using a purposive sampling technique in accordance with the following inclusion criteria: mothers with toddlers aged 6–59 months, willing to participate by signing an informed consent, and participating in the entire activity from start to finish. The intervention consisted of a 120-minute nutrition counseling session through interactive lectures, group discussions, and menu preparation demonstrations using local food ingredients. The assessment instrument used a structured questionnaire on B2SA knowledge and “Isi Piringku” (My Plate) consisting of 10 multiple-choice items with a score of 0–100). Measurements were taken before the counseling session (pre-test) and after the counseling session (post-test). In addition to the questionnaire, a participant observation sheet was used to record participant involvement during the intervention. Comparisons of pre-test and post-test scores were analyzed using the Wilcoxon Signed Rank Test at a significance level of α=0.05. Percentage changes in knowledge and attitudes were calculated to determine the trend of improvement. Results: The median level of knowledge of respondents before the counseling session was 9.00, with a range of 2-10 points, and after the counseling session, the median score was 10, with a range of 4-10 points. The statistical test yielded a Z-value of -3.483 with a p-value of 0.001. Conclusion: The "Isi Piringku" (B2SA)-based nutrition counseling program, utilizing local foods, has been shown to have a positive and significant impact on improving the knowledge of mothers of toddlers. Nutrition education with a participatory, contextual approach, and based on local potential is an effective strategy for accelerating community nutrition improvement. Suggestion: Mothers of toddlers are encouraged to apply the "Isi Piringku" (B2SA) principles with local foods (cassava, corn, bananas, fish, and moringa leaves). Community health centers (Puskesmas) and the Health Office are recommended to make this counseling model a priority program for stunting reduction, integrated with integrated health posts (Posyandu) and cadre training. Keywords: B2SA; Balanced nutrition; Local foods; Maternal knowledge; Nutrition counseling; Toddlers Pendahuluan: Indonesia masih menghadapi tantangan serius berupa beban gizi tiga kali lipat (triple burden malnutrition), terutama di wilayah perdesaan seperti Desa Hajimena, Lampung Selatan. Minimnya akses informasi gizi dan pemanfaatan pangan lokal yang belum optimal menjadi kendala utama dalam praktik pemberian makan balita. Prinsip pangan Beragam, Bergizi, Seimbang, dan Aman (B2SA) yang dituangkan dalam konsep "Isi Piringku" hadir sebagai pendekatan strategis untuk mengatasi permasalahan tersebut. Tujuan: Untuk mengevaluasi efektivitas penyuluhan gizi dan tingkat pengetahuan ibu berbasis prinsip B2SA dengan memanfaatkan potensi pangan lokal dalam upaya pemenuhan gizi seimbang bagi balita. Metode: Kegiatan dilaksanakan pada Rabu, 21 Januari 2026, di Posyandu Cemara Kebun Bibit, Desa Hajimena, Kabupaten Lampung Selatan. Penelitian ini menggunakan pendekatan one group pre-test and post-test design. Mendapatkan sampel sebanyak 36 responden yang diambil dengan teknik purposive sampling sesuai dengan kriteria inklusi: ibu memiliki balita usia 6–59 bulan, bersedia menjadi responden dengan menandatangani informed consent, dan mengikuti seluruh rangkaian kegiatan dari awal hingga akhir. Intervensi berupa penyuluhan gizi berdurasi 120 menit melalui ceramah interaktif, diskusi kelompok, dan demonstrasi penyusunan menu menggunakan bahan pangan lokal. Instrumen penilaian menggunakan kuesioner terstruktur tentang pengetahuan B2SA dan “Isi Piringku” sebanyak 10 item pilihan ganda dengan skor 0–100). Pengukuran dilakukan sebelum penyuluhan (pre-test) dan setelah penyuluhan (post-test). Selain kuesioner, digunakan lembar observasi partisipatif untuk mencatat keterlibatan peserta selama intervensi. Perbandingan skor pre-test dan post-test dianalisis dengan Uji Wilcoxon Signed Rank pada tingkat signifikansi α=0.05. Perubahan persentase pengetahuan dan sikap dihitung untuk melihat kecenderungan peningkatan. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum penyuluhan mendapatkan nilai median sebesar 9.00 dengan rentang nilai 2-10 poin dan setelah penyuluhan mendapatkan nilai median sebesar 10 dengan rentang nilai 4-10 poin. Uji statistik mendapatkan nilai Z sebesar -3.483 dengan pValue 0.001. Simpulan: Program penyuluhan gizi berbasis pendekatan B2SA "Isi Piringku" dengan memanfaatkan pangan lokal terbukti memberikan dampak positif dan signifikan terhadap peningkatan pengetahuan ibu balita. Edukasi gizi dengan pendekatan partisipatif, kontekstual, dan berbasis potensi lokal menjadi salah satu strategi efektif dalam percepatan perbaikan gizi masyarakat. Saran: Ibu balita diharapkan mengaplikasikan prinsip B2SA "Isi Piringku" dengan pangan lokal (singkong, jagung, pisang, ikan, daun kelor). Puskesmas dan Dinas Kesehatan direkomendasikan menjadikan model penyuluhan ini sebagai program prioritas penurunan stunting, terintegrasi dengan Posyandu dan pelatihan kader.